2014
DOI: 10.3906/sag-1301-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of L-carnitine in a rat model of retinopathy of prematurity

Abstract: Almagro et al. (2009) showed, under Mediterranean conditions, different soil CO 2 effluxes between land uses and, within uses, between beneath-and intercanopy sites. These findings have been weakly explained by soil temperature regime or soil water content, suggesting that microbial activity, as with other factors, could play a role in the soil C dynamic.Soil microbial properties are known to exhibit high space-time variability (Cavigelli et al., 2005). Understanding the spatial variability of soil properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
1
3
0
1
Order By: Relevance
“…In an experimental animal study that investigated the effects of L-carnitine on oxygen-induced retinopathy, the authors found that L-carnitine supplementation offered protection against retinopathy development, a finding that is in line with our findings [18]. Although ROP was observed to be approximately two times higher in the group that did not receive carnitine, this difference was not significant in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In an experimental animal study that investigated the effects of L-carnitine on oxygen-induced retinopathy, the authors found that L-carnitine supplementation offered protection against retinopathy development, a finding that is in line with our findings [18]. Although ROP was observed to be approximately two times higher in the group that did not receive carnitine, this difference was not significant in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Yousry et al [ 22 ] noted an improvement in chronic heart failure treated with sage oil as a curative rather than prophylactic measure. ROS are generated in the heart by normal mitochondrial functions as well as by enzymatic reactions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, reactive oxygen species are produced during normal cellular functions of mitochondria during oxidative phosphorylation as well as enzymatic reactions catalyzed by xanthine oxidase, NAD(P)H oxidases, and cytochrome P450 [ 35 ]. As the oxidative status of the cardiac tissue was assessed following TRZ treatment, a diminished catalase activity and increased MDA levels were reported, as well as a decrease in total thiol levels, when compared to the control, LC, and LC + TRZ groups.…”
Section: Discussionmentioning
confidence: 99%